A preliminary study of spatial distribution and plant density in a leucaena-grass planting in north Corrientes, Argentina - Gandara, Luis (2019)
In northeast Argentina, most beef cattle graze naturalized range pastures continuously, with limited winter supplementation and restricted access to improved pastures. Calving rates are low, averaging 40‒50% annually and calf weaning weights average 150‒170 kg at 6 months. Overall, productivity remains low (30‒40 kg LW/ha/yr), mainly due to poor cattle nutrition (Goldfarb et al. 1993; Goldfarb and Casco 1994). In past decades, several improved grass and legume species were evaluated as a strategy to overcome this problem (Goldfarb et al. 1993; Goldfarb and Casco 1998) with Leucaena leucocephala (leucaena) showing definite potential.